2020
DOI: 10.1159/000510907
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Lifestyle as Risk Factors for Carotid Artery Disease: A Prospective Cohort Study

Abstract: <b><i>Background:</i></b> Stroke is one of the leading causes of death, and out of all stroke cases, 10–15% originate from a previously asymptomatic stenosis in the internal carotid artery. <b><i>Aims:</i></b> The aim of the study was to investigate whether dietary and lifestyle habits were associated with future risk of incident carotid artery disease (CAD). <b><i>Methods:</i></b> Baseline examinations on middle-aged individuals (<i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The available data so far suggests that a more vegetable-fruit based diet may be more protective against the development of EC, but data supporting a recommendation along these lines for EC protection remains elusive. To reduce red meat intake and to eat more fruit and vegetables (in moderation) is supported, since doing so prevents other forms of cancer and prevents other life-threatening diseases [ 203 , 204 , 205 , 206 , 207 , 208 ], presumably because doing so reduces an individual’s body mass and changes body composition whilst providing essential vitamins and minerals that cannot be obtained from meat products [ 209 , 210 ].…”
Section: Dietary Factorsmentioning
confidence: 99%
“…The available data so far suggests that a more vegetable-fruit based diet may be more protective against the development of EC, but data supporting a recommendation along these lines for EC protection remains elusive. To reduce red meat intake and to eat more fruit and vegetables (in moderation) is supported, since doing so prevents other forms of cancer and prevents other life-threatening diseases [ 203 , 204 , 205 , 206 , 207 , 208 ], presumably because doing so reduces an individual’s body mass and changes body composition whilst providing essential vitamins and minerals that cannot be obtained from meat products [ 209 , 210 ].…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Similar to the traditional risk predictors, these carotid atherosclerosis biomarkers are also associated with several nutrition-based components [147][148][149]. Several studies have indicated a regression in cIMT by adhering to the Mediterranean diet in patients with elevated cIMT [150][151][152].…”
Section: Nutrition and Carotid Imtmentioning
confidence: 84%
“…Similarly, their study indicated a direct association of cIMT with the total (β = 0.004, p = 0.028) and saturated fat intake (β = 0.012, p = 0.006). It has been proved that intake of green vegetables, fresh, nutritious foods, fruits, and water reduces the cIMT and indicated reduced serum cholesterol levels [147,148].…”
Section: Nutrition and Carotid Imtmentioning
confidence: 99%
“…A high diet quality was associated with lower incidence of cardiovascular events in terms of myocardial infarction or ischemic stroke with follow up to 2008 in the Malmö Diet and Cancer Study (MDCS) [5]. A healthy diet and adherence to recommended levels of fiber intake were associated with a reduced risk of incident peripheral artery disease in MDCS [6], whereas no association was found between diet quality and incident carotid artery disease [7], but this study was probably underpowered. Current smoking, low diet quality and low physical activity level were associated with atherothrombotic ischemic stroke in MDCS [8].…”
Section: Introductionmentioning
confidence: 82%